1993
DOI: 10.1002/tox.2530080102
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to antibiotics and heavy metals in escherichia coli from marine fish

Abstract: Escherichia coli isolated from the intestinal tract of marine fish captured along polluted beaches of the city of Rio de Janeiro, Brazil, were investigated in terms of resistance to seven antibiotics and to four heavy metals. Approximately 40% of the strains were resistant to one or more antibiotics, with predominance of mono‐ and biresistance. Overall resistance to heavy metals was 70.7%, and exclusive resistance to these elements was more elevated than resistance to antibiotics only. Resistance to mercury wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…In the Hg-tolerant strains from the CSS the overall rate of resistance was 33.6%, a value similar to that of Ag-tolerant strains from the hospital sewage. These results are consistent with reports on the frequent association between tolerance to Hg and antimicrobial resistance found in strains isolated from different sources (22,24,26,28,41). Probably this is due to the fact that genes that code for antibiotic resistance and genes that code for mercury resistance are often carried on the same plasmids or other mobile genetic elements (41,42), favouring the occurrence of co-selective processes in the presence of this metal or of antimicrobial drugs.…”
Section: Resultssupporting
confidence: 93%
“…In the Hg-tolerant strains from the CSS the overall rate of resistance was 33.6%, a value similar to that of Ag-tolerant strains from the hospital sewage. These results are consistent with reports on the frequent association between tolerance to Hg and antimicrobial resistance found in strains isolated from different sources (22,24,26,28,41). Probably this is due to the fact that genes that code for antibiotic resistance and genes that code for mercury resistance are often carried on the same plasmids or other mobile genetic elements (41,42), favouring the occurrence of co-selective processes in the presence of this metal or of antimicrobial drugs.…”
Section: Resultssupporting
confidence: 93%
“…Earlier investigations reported that approximately 40% of E. coli strains isolated from the intestinal tract of marine fish captured along polluted beaches of Saopaulo were resistant to one or more antibiotics (Alves de Lima and Hofer, 1993). Ogbondeminu and Olayemi (1993) also found 55.9% enteric isolates from fish which were resistant to three to four antibacterial drugs.…”
Section: Resultsmentioning
confidence: 99%
“…However, only few studies have attempted to focus on the resistant bacteria in the wild fishes (Alves de Lima and Hofer, 1993;Miranda and Zemelman, 2001;Matyar et al, 2004). Digha (21 0 37'N, 87 0 33'E) situated in the coastal line of Bay of Bengal is one of the largest fish landing centre of West Bengal, India.…”
mentioning
confidence: 99%
“…In this context, the use of E. coli as a sanitary indicator for fish samples has been first reported in the 1930s [21] and since then widely applied as a microbiological quality parameter, especially on what fecal contamination is concerned [22][23][24][25].…”
Section: Escherichia Coli In Fishmentioning
confidence: 99%